Synthesis of 2-{2-[5(4)-aryl-2H-[1,2,3]-triazol-4(5)-yl]vinyl}chromen-4-ones - Albuquerque, Hélio (2014)
Chromones are a family of oxygen-containing heterocyclic compounds that have been shown particular relevant biological activity. In what concerns to 2-methylchromones, their reactivity is well-known and allowed to exploit many different kinds of chemical reactions. The acidic character of the 2-methyl group, due to the low electron density at C-2 caused by carbonyl group enable this class of compounds to undergo oxidation, photolysis, cycloaddition and condensation reactions